SCHOOL CLIMATE, PRINCIPAL MANAGERIAL STYLES AND ORGANISATIONAL COMMITMENT AMONG JUNIOR SECONDARY SCHOOL TEACHERS IN OYO STATE, NIGERIA - Oredein , Afolakemi O.; Bello, Elizabeth O. (International Journal of Research -GRANTHAALAYAH, 2022)
This study seeks to investigate the influence of school climate and principal managerial styles on organisational commitment in public junior secondary schools in Oyo State, Nigeria. A descriptive research design survey type was adopted in this study. Three research questions were raised and answered, while two hypotheses were formulated and tested at a 0.05 per cent level of significance. The population consisted of 604 principals and 14,508 teachers from public junior secondary schools in Oyo state. The multistage sampling procedure uses the Simple Random Sampling technique to select 316 principals and 2,960 teachers. A mixed-method of two validated questionnaires, SCMSOCQ (α = 0.87), MSPQ (α = 0.89), and Key Informant Interview (KII) were used to collect data. The descriptive statistics of mean and percentages were used to analyse the demographic variables while inferential statistics of Factorial ANOVA were used to test hypotheses at a 0.05 level of significance. Discourse analysis was used for the interview. The result revealed that the transformational managerial style is mostly adopted by principals (weighted mean=3.38). Also, there is no interaction between school climate, and principal managerial styles but both are significant to organizational commitment (P<0.05). Based on the findings the study concludes that school climate and principal managerial styles can influence organisational commitment among public junior secondary school teachers in Oyo State. However, based on the results, recommendations were made to improve school climate and principals’ managerial styles that will enhance organisational commitment domain among public junior secondary school teachers in Oyo State.